Pengaruh Penggunaan Proton Pump Inhibitors (PPIs) Jangka Panjang terhadap Kanker Lambung - Christi D. Mambo; Anglina S. R. Masengi; Fellery W. R. Onibala (Universitas Sam Ratulangi, 2024)
Abstract: Proton pump inhibitors (PPIs) are the most commonly used group of drugs for the treatment of acid-related disorders, such as gastro-esophageal reflux disease (GERD), peptic ulcer disease (PUD), and dyspepsia. In Indonesia overall, in recent years there has been a reported increase in the use of PPIs and the associated side effects of long-term use including gastric cancer. This study aimed to determine the effect the long-term use of PPIs on the occurrence of gastric cancer. This was a literature review study. Journal searching was conducted through two online journal databases, namely, PubMed and ScienceDirect. The results obtained 11 research articles about the duration of PPIs’s use as a cause of gastric cancer. Long-term use of PPIs was associated with an increased risk of gastric cancer, which was also associated with the duration of use. Gastric cancer due to long-term use of PPIs could also occur in patients after H. pylori eradication, patients with GERD, and patients after percutaneous coronary interventions (PCI). In conclusion, long-term use of PPIs can affect the occurrence of gastric cancer. Keywords: proton pump inhibitors; gastric cancer; long-term use of drug Abstrak: Proton pump inhibitors (PPIs) merupakan golongan obat yang paling umum digunakan untuk pengobatan terkait gangguan yang berhubungan dengan asam lambung seperti gastro-esophageal reflux disease (GERD), peptic ulcer disease (PUD), dan dyspepsia. Di Indonesia secara keseluruhan beberapa tahun terakhir dilaporkan terjadi peningkatan penggunaan PPIs yang memunculkan efek samping terkait penggunaan jangka panjang termasuk kanker lambung. Penelitian ini bertujuan untuk mengetahui pengaruh jangka waktu penggunaan PPIs pada kejadian kanker lambung. Jenis penelitian ialah suatu literature review dengan pencarian jurnal melalui dua database journal online, yaitu PubMed dan ScienceDirect. Hasil penelitian mendapatkan 11 artikel penelitian yang memiliki informasi terkait jangka waktu penggunaan PPIs sebagai penyebab kanker lambung. Penggunaan PPIs jangka panjang berhubungan dengan peningkatan risiko kanker lambung, yang juga berhubungan dengan durasi penggunaan. Kanker lambung akibat penggunaan PPIs jangka panjang juga dapat terjadi pada pasien setelah eradikasi H. pylori, pasien dengan GERD, dan pasien setelah percutaneous coronary interventions (PCI). Simpulan penelitian ini ialah terdapat pengaruh penggunaan PPIs jangka panjang terhadap terjadinya kanker lambung. Kata kunci: proton pump inhibitors; kanker lambung; penggunaan obat jangka panjang